Wirtualne symfonie dla każdego – muzyka w cyberprzestrzeni - Skrzydlewski, Wojciech (Studia Edukacyjne, 2021)
The article presents selected issues regarding the role of popular music. The following issues are addressed: the development of phonography from its mechanical form to the modern, virtual one, changes in professional music creation, the role of new media in functioning of musicians, and music as a medium of generational influence. Changes in the operation of show business in the context of the development of new media and pandemics were also shown.